2007
DOI: 10.1063/1.2813622
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative digital detection of magnetic beads using pseudo-spin-valve rings for multiplexed bioassays

Abstract: We present a magnetic multiplexed assay technology which encodes the identities of target biomolecules according to the moment of magnetic beads to which they are attached. An active digital technique based on a microfabricated magnetoresistive ring-shaped sensor is demonstrated, which can distinguish the magnetic moments of micron-sized superparamagnetic beads. We propose that this development is key to combining nonvolatile magnetic labeling with biochemical libraries for high-throughput bioassays and rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 19 publications
0
35
0
Order By: Relevance
“…Domain walls in nanotracks can be used to reversibly capture and transport SPM microbeads, [17][18][19][20][21][22][23]26 and it was recently shown that DWs can also be used to sense the presence of individual beads. 13,17,26 Llandro et al 13 demonstrated the detection of individual beads by measuring the effect of their stray field on DW-mediated magnetization switching in pseudo-spin-valves. 33 Vavassori et al 17 exploited the magnetic focusing action of DWs to position a bead near a DW trapped at a nanotrack corner, and then detect the bead's presence based on a small change in the DW depinning field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Domain walls in nanotracks can be used to reversibly capture and transport SPM microbeads, [17][18][19][20][21][22][23]26 and it was recently shown that DWs can also be used to sense the presence of individual beads. 13,17,26 Llandro et al 13 demonstrated the detection of individual beads by measuring the effect of their stray field on DW-mediated magnetization switching in pseudo-spin-valves. 33 Vavassori et al 17 exploited the magnetic focusing action of DWs to position a bead near a DW trapped at a nanotrack corner, and then detect the bead's presence based on a small change in the DW depinning field.…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23]26 By integrating a single-bead detection mechanism into such DW-based transport structures, microscale sorting and sensing of single cells or biomolecules could be simultaneously achieved in magnetic lab-on-a-chip devices. Magnetoresistive sensors, which exhibit a perturbed response to applied excitation fields due to the presence of beads at the sensor surface, [1][2][3][13][14][15][16][17] form the basis for most SPM bead sensing platforms. On-chip bead-based sensing of biomolecules with such devices usually relies on chemical functionalization of the sensor surface for preferential capture and immobilization of magnetic marker beads that bind the chemical target in the host fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The central element of a magnetic biosensor is a detector for the stray or 'fringing' magnetic fields generated by magnetised MNPs which are used to label, typically in-vitro, analytes of interest within a biological sample. Previously used sensors include SQuIDs 6 , Hall sensors 7 , ferromagnetic rings 8,9 and magneto-impedance devices 10 . However one of the most widely used methods is that employing magnetoresistive (MR) magnetic field sensors [1][2][3][4][5][11][12][13][14] which are typically fabricated with at least one lateral dimension on the order of 10-100 µm.…”
mentioning
confidence: 99%
“…6,7 The ring geometry offers some advantages in MRAM applications due to its stability on reducing the memory element size. 10 However, most of the previous studies on magnetic rings were focused on a single magnetic layer [5][6][7][8] or GMR spin-valves. 9 There are few reports on MTJ rings, 11,12 and none on MgO-based MTJ rings with high TMR.…”
mentioning
confidence: 99%
“…However, another stable magnetic state, namely the vortex state, may form in microstructured magnetic rings [5][6][7][8] and discs, 9 in order to minimize the magnetostatic energy of the system. Ring-shaped magnets with larger diameters and ring width exhibit more complex metastable states.…”
mentioning
confidence: 99%